The Food Crisis in Egypt and the Decline and Fall of Germanicus - Graham, Dr Daryn (Journal of Historical Studies, 2021)
Purpose: The purpose of this article is to provide an evidence-based and fully examined unique and original account of the decline and fall of Germanicus, and the role the food crisis of Egypt in the early years of the principate of Tiberius played in that decline and fall. Methodology: No doubt, that decline and fall may have arguably saved the Roman Empire from civil was between Tiberius and Germanicus in time, but this article finds that Germanicus' swift intervention in Egypt saved Egypt, and perhaps parts of the empire, from potential acute food shortage and even famine and starvation. In terms of methodology, these issues are explored throughout this article, as are the relationship between Tiberius the Roman Senate, and the aftermath of the AD17 earthquake in the Roman province of Asia, and their relating influences over decline and fall of Germanicus, as well. Findings: Still, this article finds that Germanicus' swift salvation of Egypt from famine and starvation rivalled Tiberius' rebuilding of the province of Asia after AD17 too closely, earning the emperor's rebuff and rebuttals, leading to the young Prince's fall from imperial favour, and hence, his premature death.